2021
DOI: 10.22541/au.163256737.76393954/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Giving the gift of life twice”: Understanding the lived experiences of parent donors and non-donors in pediatric haploidentical hematopoietic cell transplantation

Abstract: Background: The use of parental donors in pediatric haploidentical hematopoietic cell transplantation is increasing, but research on the psychosocial impact of parental donation is currently limited. We conducted a retrospective, qualitative study to explore parental perceptions of the donation process and the impact of being a donor (or non-donor) on parents’ adjustment and coping with their child’s transplant experience. Methods: Parents/caregivers of children who underwent transplantation with a parental do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In line with these findings, in a qualitative study involving parents from the anticipation stage to the completion of their child's HSCT, participants consistently reported numerous positive outcomes despite facing significant difficulties. These benefits encompassed increased spirituality, gaining a new perspective on life, strengthening parent-child relationships, a greater appreciation for life, and a desire to help families whose children will undergo this process in the future (Schaefer et al, 2022). In another qualitative study, it was identified that parents of children receiving HSCT developed a desire to help others, felt empathy toward others, established stronger relationships with their spouses, family members, and acquaintances, and acquired newfound personal strength to endure life's hardships (Beckmann et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, in a qualitative study involving parents from the anticipation stage to the completion of their child's HSCT, participants consistently reported numerous positive outcomes despite facing significant difficulties. These benefits encompassed increased spirituality, gaining a new perspective on life, strengthening parent-child relationships, a greater appreciation for life, and a desire to help families whose children will undergo this process in the future (Schaefer et al, 2022). In another qualitative study, it was identified that parents of children receiving HSCT developed a desire to help others, felt empathy toward others, established stronger relationships with their spouses, family members, and acquaintances, and acquired newfound personal strength to endure life's hardships (Beckmann et al, 2021).…”
Section: Discussionmentioning
confidence: 99%